The impact of assessment on constructive alignment of a modern veterinary curriculum - Cobb, Kate (2015)
Constructive alignment (CA) describes an approach to education where teaching, learning and assessment are aligned to allow the learner to achieve the intended learning outcomes (ILOs) of the course. Assessment has a strong influence on learning and therefore the potential to have either a positive or negative impact on CA. The aim of the research in this thesis is to explore the effects of assessment on CA. The context for the research is the final year of study within the School of Veterinary Medicine and Science (SVMS), at the University of Nottingham. Five mixed methods studies were conducted utilising questionnaires, semi-structured interviews and focus groups. In study one the ILOs of the course were defined and subsequently used in study two as a framework for an alumni survey to determine how well prepared graduates feel for clinical practice. Studies three and four investigated the impact of assessments on learning behaviour, namely multiple-choice questions (MCQ), directly observed procedural skills (DOPS) and the script concordance test (SCT). Finally in study five the influence of the transition to practice on learning behaviour during final year was explored. Graduates felt well prepared by the SVMS curriculum for a career in practice with respect to all ILOs. However, assessments were not rated so highly when considered alone. DOPS and to some extent the SCT are considered to be authentic assessment formats and encourage a deep approach to learning. The MCQ in this context results in surface learning strategies being adopted. The imminent transition to practice has a positive effect on learning behaviour, however this conflicts with the preparation required for final year examinations. Elements of the assessment strategy that have a positive and negative impact on CA are identified and discussed. Changes to the curriculum are proposed to enhance CA and ease the transition to practice.